327 To Fuse or Not to Fuse: The Elderly Patient with Lumbar Stenosis and Low-Grade Spondylolisthesis. Systematic Review and Meta-Analysis of Randomised Controlled Trials. (19th August 2022) - Abdel-Fattah, AR; Bell, F; Boden, L; Ferry, J; McCormick, C; Ross, M; Cameron, I; Smith, T; Baliga, S; Myint, P
Abstract: Aim: The optimum surgical intervention for elderly patients with lumbar spinal stenosis(LSS) and low-grade degenerative-spondylolisthesis(LGDS) has been extensively debated. We conducted a systematic review and meta-analysis of randomised-controlled-trials(RCTs) comparing the effectiveness of decompression-alone against gold-standard decompression-with-fusion(D+F) in elderly patients with LSS and LGDS. Method: A systematic literature search was performed on published databases from inception to October-2021. English-language RCTs of elderly patients (mean age over-65) with LSS and LGDS, who had undergone DA or D+F were included. The quality and weight of evidence was assessed, and a meta-analysis performed. Results: Seven RCTs (n=581; mean age:65.9 years; 59.9% female) were included. There was no difference in visual-analogue-scale(VAS) scores of back-pain(BP) or leg-pain(LP) at mean follow-up of 28.6 months between both DA and D+F groups (BP: mean-difference (MD)-0.22, 95%CI:-0.76–0.32; LP: MD:-0.26, 95%CI:-0.79–0.27). In addition, subgroup analysis of long-term follow-up (>3 years) showed lower VAS scores for BP and LP in patients who underwent DA (BP MD:-1.70, 95%CI:-2.8-(-0.60); LP MD:-1.00, 95%CI:-1.77-(-0.23)). No difference in disability, measured by Oswestry-Disability-Index(ODI) scores, was found between both groups (MD:0.50, 95%CI: -3.31–4.31). However, patients in DA group had less hospital complications and fewer adverse events (total-surgical-complications OR:0.57, 95%CI:0.36–0.90), despite a higher rate of post-operative DS (OR:8.63, 95%CI:3.35–22.26). Conclusions: DA is not inferior to D+F in elderly patients with LSS and LGDS. DA has better pain outcomes at three-years follow-up and carries lower risk hospital-complications and fewer adverse-events. Surgeons should weigh these findings with increased risk of DS-progression.